(untitled) (Experimental biology, 2021)
Antimicrobial activity of the drug FS-1 is due to the content of iodine halogen, which is quite active. Currently, potassium triiodide-based preparations, such as Lugol’s solution, Iodopyron, Betadine and others, are already used as antiseptics. Studies have already been conducted confirming the ability of FS-1 to increase the permeability of the bacterial cell membrane, which allows antibiotics to act more efficiently, and in vitro and in vivo studies have been conducted to evaluate the cytotoxicity and genotoxicity of FS-1 in laboratory animals with systemic exposure. In this experiment, effect of FS-1 on the site of primary contact, the buccal epithelium, was studied. Based on the experiment results, we could conclude about the possible use of FS-1 as an oral antiseptic. Three rabbits were used in the experiment, buccal epithelium smears of which were taken before the administration of 4 mg/kg FS-1 (control samples) and after the administration of FS-1 (experimental samples). Total period of FS-1 daily administration was 14 days, which is a period for self-renewal of the epithelium. Obtained smears of the cells were examined under a microscope for the presence of cytogenetic aberration. As a result, there was no significant change after administration of FS-1, since the level of cells with karyolysis, karyorrhexis, micronuclei, and nuclear protrusions remained at about the same level. Therefore, it was concluded that FS-1 does not cause cytogenotoxic effect upon prolonged exposure to rabbit buccal epithelium.